2021
DOI: 10.1002/acp.3822
|View full text |Cite
|
Sign up to set email alerts
|

When and how seductive details harm learning. A study using cued retrospective reporting

Abstract: We investigated the processes that make seductive details (i.e., interesting but irrelevant pictures and text passages in learning materials) harmful for learning scientific concepts and principles. In our experiment, students (N = 113) learned without seductive details (control condition) or with seductive details, and afterwards worked on a knowledge test. They then retrospectively verbalized their thoughts during learning while watching a replay of their eye-movements during the learning session (cued retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 37 publications
(88 reference statements)
5
15
0
Order By: Relevance
“…Harp and Mayer ( 1998 ) found seductive details being detrimental to learning when they were presented early but not late in the instruction suggesting that presenting seductive details early primed inadequate prior knowledge and led to deeper processing of irrelevant details at the expense of pertinent content. In a similar vein, Eitel et al ( 2019 ) and Bender et al ( 2021 a) found that seductive details hampered learning only when students (mistakenly) considered them relevant for learning, which presumably led to increased prior knowledge activation and deeper processing of seductive details. Similar assumptions can be made based on the construction-integration model (Kintsch, 1998 ).…”
Section: Seductive Details Hamper Learning Even When They Do Not Disruptmentioning
confidence: 84%
“…Harp and Mayer ( 1998 ) found seductive details being detrimental to learning when they were presented early but not late in the instruction suggesting that presenting seductive details early primed inadequate prior knowledge and led to deeper processing of irrelevant details at the expense of pertinent content. In a similar vein, Eitel et al ( 2019 ) and Bender et al ( 2021 a) found that seductive details hampered learning only when students (mistakenly) considered them relevant for learning, which presumably led to increased prior knowledge activation and deeper processing of seductive details. Similar assumptions can be made based on the construction-integration model (Kintsch, 1998 ).…”
Section: Seductive Details Hamper Learning Even When They Do Not Disruptmentioning
confidence: 84%
“…Because these indicators can mirror the combined effects of several ongoing cognitive processes (Anmarkrud et al, 2019 ; Kok & Jarodzka, 2017 ), deciphering the cognitive meaning of learners’ visual attention distribution based solely on eye tracking technology can be difficult. Future research could triangulate eye tracking data with additional measurement approaches, such as cued retrospective reporting (Bender et al, 2021 ), to minimise ambiguity and avoid misinterpretation of eye movement indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Using a cue can elicit a better recollection of what happened during the task ( van Gog et al, 2006 ). Eye-movement videos were previously used in various studies with retrospective verbal protocols (e.g., Bender et al, 2021 ; Greussing et al, 2020 ; Muntinga & Taylor, 2018 ; Penttinen et al, 2013 ) and efficiently helped subject recall their cognitive processes. Cued retrospective interviews were used in previous studies about strategies used by musicians during improvisations ( Després et al, 2017 ; Norgaard, 2011 ), which led us to believe this approach was suitable for another in situ musical task, a sight-singing exercise presented in a context similar to end-of-semester aural skills evaluations in higher education.…”
Section: The Current Studymentioning
confidence: 99%